1995
DOI: 10.1128/iai.63.10.4029-4033.1995
|View full text |Cite
|
Sign up to set email alerts
|

Lack of a role for natural killer cells in early control of Brucella abortus 2308 infections in mice

Abstract: Studies were conducted to determine if natural killer (NK) cells are important for early control of the virulent strain Brucella abortus 2308 following infection of mice with high or low challenge doses. Splenocytes from C57BL/10 and BALB/c mice that had been infected with the lower dose of B. abortus displayed increased cytotoxicity against YAC-1 cells during the first week after infection, while infection of C57BL/10 mice with the higher challenge dose either did not alter the level of NK cytotoxic activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…Yet, although it has been demonstrated in vitro that human NK cells are able to kill Brucella suis ‐infected macrophages; this occurs independently of the down‐modulation of MHC‐I molecules (Dornand et al ., ). Moreover, humans with acute brucellosis have suppressed NK activity (Salmeron et al ., ) which, together with results in mice showing no role of NK in the control of infection (Fernandes et al ., ), would support the contention that NK cells – as innate immune cells – would play no relevant function in controlling a slowly replicating organism such as Brucella spp., which causes chronic infections (Baldwin and Goenka, ).…”
Section: Discussionmentioning
confidence: 79%
“…Yet, although it has been demonstrated in vitro that human NK cells are able to kill Brucella suis ‐infected macrophages; this occurs independently of the down‐modulation of MHC‐I molecules (Dornand et al ., ). Moreover, humans with acute brucellosis have suppressed NK activity (Salmeron et al ., ) which, together with results in mice showing no role of NK in the control of infection (Fernandes et al ., ), would support the contention that NK cells – as innate immune cells – would play no relevant function in controlling a slowly replicating organism such as Brucella spp., which causes chronic infections (Baldwin and Goenka, ).…”
Section: Discussionmentioning
confidence: 79%
“…Other than neutrophils, activated NK cells also kill infected targets and act as first line of defense against Brucella (Fernandes et al, 1995 ). Brucella activate NK cells by inducing antigen presenting cells to release IL-2 and NK cells are converted into killer cells by IL-2 activation, secretion of IFN-γ and production of IFN-γ which plays an important role in developing a Th1- or Tc1-like response (Gao et al, 2011 ).…”
Section: Brucella Modulation Of Innate Immune Responsementioning
confidence: 99%
“…8 Murine models of Brucella infection have shown that a type 1 T helper (Th1) cell cytokine response is necessary for clearance of infection. 13,97 This Th1 response has been shown to be elicited by triggering toll-like receptor 9 (TLR9). 125 The ligand for TLR9 is unmethylated DNA, and heat-killed B. abortus has been shown to simulate TLR9 and induce a Th1 cascade.…”
Section: Immunitymentioning
confidence: 99%
“…98 Blockage of the Th1 cytokine cascade did not shift the response of mice to a Th2 response as IL-4 production was not elevated in the mouse splenocyte. 97 Studies in BALB/c mice, which have a marked lag in the upregulation of the Th1 response after Brucella infection, show that CD8+ T cells and TNF-α contribute to the control of Brucella infection but are not satisfactory in themselves in inducing full clearance of the organism. 97,174 However, despite a lack of measurable IL-4, blockage of both IL-4 and IL-10 pathways resulted in decreases in Brucella infection.…”
Section: Immunitymentioning
confidence: 99%
See 1 more Smart Citation